The importance of early phonics improvements for predicting later reading comprehension. (17th July 2019) - Double, Kit S.; McGrane, Joshua A.; Stiff, Jamie C.; Hopfenbeck, Therese N.
Abstract : The role of phonics instruction in early reading development has been the subject of significant conjecture. Recently, England implemented a phonics screening check to assess the phonetic decoding of 6‐year‐old students, to ensure that all students master this foundational literacy skill and attain adequate phonemic awareness in the early years of primary schooling. Students who fail this check are obliged to retake the assessment the following year. In this article, we compare the performance of students who initially pass this check ( pass ) and students who fail the original assessment but pass the retaken assessment ( fail–pass ), with students who fail both the original and retaken assessments ( fail–fail ). Using data from the Key Stage 1 assessment of reading and the Progress in International Reading Literacy Study (PIRLS), we examined the reading comprehension performance of these students approximately 1 and 4 years after their first phonics screening. The results suggested that fail–pass students performed substantially better than fail–fail students, even after performance on the initial phonics check was controlled for. While fail–pass students do not appear to entirely catch up with pass students in reading comprehension, their relatively better performance underscores the importance of intervening for those students who are identified as having problems with phonetic decoding to increase their likelihood of success at reading comprehension in later schooling.